Association between hyperuricemia and all-cause mortality in people taken Statins: a retrospective cohort study - Zhu, Bin; He, Zijun; Wu, Mingfen; Huo, Jiping; Zhao, Zhigang; Guo, Wei; Yang, Li (Frontiers in Pharmacology, 2025)
BackgroundStatins are one of the most widely prescribed medicines in clinical practice. Their benefits have extended beyond cardiovascular applications to reduce serum uric acid levels. This study aims to investigate the relationship of hyperuricemia with the risk of all-cause mortality among individuals taking statins.MethodA retrospective cohort study was performed using data from the National Health and Nutrition Examination Survey (NHANES) database between 2005 and 2018. The weighted Cox proportional hazards models were used to investigate the relationship between hyperuricemia and all cause-mortality.ResultsA total of 1,958 participants were enrolled for analysis. Of them 1,429 participants were with normal uric acid levels and 529 people were with hyperuricemia. After 12 years of follow-up, there were 267 participants who died from all-cause mortality in the non-hyperuricemia group and 136 died in the hyperuricemia group. Additionally, 32.49% of participants took more than five kinds of medicines in the non-hyperuricemia group compared to 42.05% participants in the hyperuricemia group. Even after adjusting for confounding factors, we found that the serum uric acid (SUA) level was significantly correlated with all-cause mortality among statin users (HR = 1.13, 95% CI:1.02–1.24, p = 0.0161). Additionally, hyperuricemia resulted in significant increases in all-cause mortality relative to non-hyperuricemia participants in three models (HR = 1.51, 95% CI:1.16–1.96, P = 0.0023).ConclusionAlthough statins have been shown to reduce uric acid levels, hyperuricemia is still significantly associated with the all-cause mortality in people taking statins. Those taking statins and having hyperuricemia should pay special attention to their SUA level.